Management of Botrytis blossom blight in wild blueberries by biological control agents under field conditions. (May 2020) - Abbey, Joel A.; Percival, David; Asiedu, Samuel K.; Prithiviraj, Balakrishnan; Schilder, Annemiek
Abstract: Botrytis blossom blight is an important disease of wild blueberries in Canada that causes over 20% yield losses annually. Four trials (2 in each year) were set up in 2015 and 2016 to investigate the efficacy of biofungicides against Botrytis blossom blight in wild blueberry. Botector®, Fracture® and Serenade MAX® were evaluated alone and in rotation with Switch® and compared with a standard control program (Fontelis®, Switch®, and Pristine®). Three applications of each biofungicide were done for stand-alone treatment, and each rotated with Switch® as combined treatment. Fungicides were applied at 7-10-day intervals starting from pre-anthesis, white tip stage. Botector®, Fracture® and Serenade MAX® rotation with Switch® suppressed Botrytis blossom blight by over 65% and 60% less disease incidence and severity compared to the untreated control. Significant disease suppression was observed in stand-alone application of Botector®, Fracture® and Serenade MAX® in 2016 whereas they were not effective in 2015. The rotation of Fracture® and Serenade MAX® with Switch®, and stand-alone Serenade MAX® resulted in increased harvestable berry yield. The results suggest that the use of biofungicides in tandem with conventional fungicides in an integrated disease management program, can adequately suppress Botrytis blossom blights. Highlights: Botector®, Fracture® and Serenade MAX® have the potential of suppressing Botrytis blossom blight. Fracture® and Serenade MAX® rotation with Switch® significantly suppressed Botrytis blossom blight in wild blueberry. Biofungicide rotation with synthetic fungicide provided disease control similar to that of synthetic fungicide application.